Residents' willingness to pay for mitigation measures: The case of tourism impacts in Tel Aviv's neighborhoods - Amit Birenboim; Michal Zuckerman Farkash; Aliza Fleischer (Annals of Tourism Research Empirical Insights, 2022)
Destinations wishing to develop new sustainable tourism strategies have to adopt proactive measures in order to address potential adverse impacts of tourism. Using a discrete choice approach, we investigated residents' preferences and willingness to pay for municipal programs that mitigate such future tourism-related concerns in Tel Aviv. Results indicate that residents who live nearby the tourist center commonly perceive tourism impacts as more severe, but do not necessarily favor interventions that mitigate these impacts. Furthermore, both perception of impacts and preferences for mitigation measures were found to be heterogeneous and associated with socio-economic characteristics and geographical proximity to the tourism center. Therefore, the study informs researchers and policymakers to consider generating neighborhood-specific intervention strategies when considering future sustainable tourism development.
Keywords: 330; Mitigation strategies; Discrete choice analysis; Willingness to pay; Overtourism; residents' attitudes